Uji Potensi Antibakteri dan Antibiofilm Minyak Atsiri Umbi Teki (Cyperus rotundus L.) terhadap Staphylococcus aureus ATCC 6538 - Uthari, Ni Made; Soegianto, Lisa; Hermanu, Liliek S. (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2017)
Infectious disease is a disease that is caused by an invasion of pathogenic microorganisms in the body. Biofilm is a group of microorganisms that are able to differentiate and proliferate in the complex way as well as being able to communicate between cells through a matrix of polysaccharides. In chronic infection, biofilm has an important role to maintain the bacteria which can cause resistance to antibiotics. Teki (Cyperus rotundus L.) is one of the plants that has many benefits for different treatment. The aim of this study was to determine the antibacterial activity and inhibition of biofilm activity of essential oil of Cyperus rotundus L. tubers against Staphylococcus aureus. Essential oil was extracted by distillation using Stahl with water as the solvent and the yield of essential oil obtained was 0.22%. Determination of antibacterial activity and antibiofilm activity were carried out by microdilution method using microplate 96 U-PVC bottom wells against Staphylococcus aureus which is equivalent to the solution standard of ½ Mc Farland I. The results of antibacterial activity tests showed that MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration) values were 0.05% (v/v) and 12.5% (v/v). Antibiofilm activity test showed that the essential oil of Cyperus rotundus L. tubers is able to inhibit 89.01% of the biofilm formation of Staphylococcus aureus on the concentration of 0.09% (v/v).